ADJUSTMENT OF PHARMACOLOGICAL ANTIARRHYTHMIC THERAPY IN PATIENTS WITH PAROXYSMAL ATRIAL FIBRILLATION DURING SERIAL TESTING OF ANTIARRHYTHMIC DRUGS WITH TRANSESOPHAGEAL ELECTROPHYSIOLOGICAL STUDIES - K. A. Skiba; V. V. Petry; V. A. Sulimov (Российский кардиологический журнал, 2003)
The work has studied opportunities for ТЕ EPS in serial testing of antiarrhythmic drugs testing to prevent recurrent arrhythmia in patients with atrial fibrillation. Antiarrhythmic drug adjustment was performed in 85 patients with paroxysmal atrial fibrillation. Serial testing implied the usage of all 4 series of antiarrhythmic drugs. Individual effective antiarrhythmic therapy was adjusted in 83 (98 %) patients. Class I drug appeared to be most effective (in 89 % patients) with the best individual result for Cordarone which achieved effect in 61 % cases when administered as 600-800 mg daily. To obtain most reliable results of pharmacological antiarrhythmic therapy adjustment in patients with paroxysmal atrial fibrillation during diagnostic transesophageal electrical stimulation (TEES) and during serial testing of antiarrhythmic drugs it is rational to use "non-aggressive" methods of atrial fibrillation induction: accelerating, frequent and programmed atrial stimulation with one or two delayed stimuli.